Autonomous Motivation: The Unresolved Issue in Student Engagement - Nara Sari (IC-ITECHS, 2020)
Education in the pandemic era has forced teachers and students to face multiple challenges in learning. Student engagement in distance learning has become a recent issue in EFL teaching. Preliminary investigations suggest that both synchronous and asynchronous learning will be less beneficial without student active involvement in the learning process. In fact, engaged students can achieve better since they are highly motivated and passionate about attaining the learning outcomes. Observations and qualitative surveys were conducted to investigate student autonomous motivation in studying Psycholinguistics online. The participants were currently trained to be EFL teachers at a private university in Indonesia. Therefore, as prospective teachers, it was assumed that the students had possessed sufficient motivation and autonomy before being enrolled in the course. However, the results of the study showed that the students struggled to understand the materials taught in the Psycholinguistics course since it required a lot of independent reading. Group work was not very effective in improving student achievement in the classroom, yet group presentation allowed students to exchange ideas, share experiences with peers and improve understanding of a particular subject matter.